2020
DOI: 10.1186/s13568-020-01015-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of isoxanthohumol bioconversion from spent hops into 8-prenylnaringenin using resting cells of Eubacterium limosum

Abstract: Hops is an almost unique source of the potent phytoestrogen 8-prenylnaringenin (8-PN). As hops contain only low levels of 8-PN, synthesis may be more attractive than extraction. A strain of the Gram-positive Eubacterium limosum was isolated previously for 8-PN production from more abundant precursor isoxanthohumol (IX) from hops. In this study, spent hops, an industrial side stream from the beer industry, was identified as interesting source of IX. Yet, hopderived compounds are well-known antibacterial agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…They concluded that 8-prenylnaringenin was the most powerful estrogen molecule formed via the chemical isomerization of desmethylxanthohumol. Moens et al [49] produced 8-prenylnaringenin via bioconversion in an enzymatic route from xanthohumol extracted from spent hops. Jerkovic and Collin [60] used spent hops to produce resveratrol-enriched extracts, reaching 7.7 and 0.7 mg/kg trans-piceid and trans-resveratrol via ethanolic solution (50% v/v), respectively.…”
Section: Hot Trub and Spent Hops As A Source Of New Productsmentioning
confidence: 99%
“…They concluded that 8-prenylnaringenin was the most powerful estrogen molecule formed via the chemical isomerization of desmethylxanthohumol. Moens et al [49] produced 8-prenylnaringenin via bioconversion in an enzymatic route from xanthohumol extracted from spent hops. Jerkovic and Collin [60] used spent hops to produce resveratrol-enriched extracts, reaching 7.7 and 0.7 mg/kg trans-piceid and trans-resveratrol via ethanolic solution (50% v/v), respectively.…”
Section: Hot Trub and Spent Hops As A Source Of New Productsmentioning
confidence: 99%
“…Two compounds that have similar pharmacokinetic profiles have revealed interesting features as their molecular masses (m/z Bacterial transformation of XN has been observed following in vitro digestion of IXN with Eubacterium limosum, which produces 8-PN. [22] Also Eubacterium ramulus is known to hydrogenate specifically the Michael system in many chalcones. [23] While this may appear to suggest that bacteria were involved in the transformation of XN to 533.1672 and 531.1883, as it has the corresponding mass of M-2H in our volunteers, certain observations contradict this.…”
Section: Identification and Pharmacokinetics Of Mixed Xanthohumol Met...mentioning
confidence: 99%
“…The 8-PN was obtained by bioconversion of isoxanthohumol(IX) from BSH using resting cells of Eubacterium limosum . BSH prenylated flavonoids have antimicrobial properties so the bacteria were used at the resting phase, at a pH of 7.8–8, and in a reinforced clostridial medium for proper enzymatic induction and maximal solubility ( Moens et al, 2020 ). Standardized extracts in 6-PN, 8-PN, IX, and XN of spent hops were administered to post-menopausal women and their pharmacokinetics was evaluated.…”
Section: Extraction Of Value-added Compounds From Spent Hopsmentioning
confidence: 99%